2020
DOI: 10.1007/s11010-020-03686-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor necrosis factor-α enhanced the antifibrotic effect of empagliflozin in an animal model with renal insulin resistance

Abstract: Insulin resistance (IR) has emerged as one of the main risk factors for renal fibrosis (RF) that represents a common stage in almost all chronic kidney disease. The present study aims to investigate the inhibitory effect of empagliflozin (EMPA "a sodium-glucose co-transporter 2 inhibitor") and infliximab [IFX "a tumor necrosis factor-α (TNF-α) antibody"] on RF in rats with induced IR. IR was induced by adding 10% fructose in drinking water for 20 weeks. Thereafter, fructose-induced IR rats were concurrently tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 79 publications
(94 reference statements)
2
18
0
Order By: Relevance
“…Nonetheless, their use in patients with rheumatoid arthritis from the KOBIO registry did not influence any change in renal function [77]. Furthermore, a study on rats has shown that a combination of empagliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, and infliximab prevented renal fibrosis to a greater extent than monotherapy, which could present a promising therapeutic option [78].…”
Section: Tumor Necrosis Factormentioning
confidence: 99%
“…Nonetheless, their use in patients with rheumatoid arthritis from the KOBIO registry did not influence any change in renal function [77]. Furthermore, a study on rats has shown that a combination of empagliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, and infliximab prevented renal fibrosis to a greater extent than monotherapy, which could present a promising therapeutic option [78].…”
Section: Tumor Necrosis Factormentioning
confidence: 99%
“…DN has early glomerular barrier and tubular dysfunction component [4,52]. Early in diabetes, the hemodynamic changes involve efferent arteriolar vasoconstriction in contrast to afferent vasodilation that ultimately increases glomerular hydrostatic pressure [17], leading to glomerular hyper ltration in diabetes [53].…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates long-term ARB inhibition in an animal model of T1D, which can delay and decrease the development of diabetic glomerulopathy, by modulating glomerular diabetes-associated hemodynamic changes. Further studies are needed to weight hemodynamic versus non-hemodynamic [12,52] factors that predominate in the pathophysiology and pathogenesis of DN in clinical practice and the starting time of ARB initiation.…”
Section: Clinical Considerationmentioning
confidence: 99%
“…An interesting study explored the possible effect of empagliflozin and infliximab, both as monotherapy and combination therapy, to rats with renal fibrosis and induced IR [ 62 ]. Thirty male Wistar albino rats were fed either with an NC diet ( n = 6, NC controls) or fructose-based diet so as to induce IR ( n = 24).…”
Section: Overweight and Obesitymentioning
confidence: 99%